A review of internet of energy based building energy management systems: Issues and recommendations - Hannan M.A.; Faisal M.; Ker P.J.; Mun L.H.; Parvin K.; Mahlia T.M.I.; Blaabjerg F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Buildings; Controllers; Cooling; Digital storage; Energy conservation; Energy efficiency; Energy management; Energy utilization; Intelligent buildings; Internet; Monitoring; Sustainable development; Three term control systems; Zero energy buildings; Building energy consumption; Building energy efficiency; Building energy management systems; Building energy systems; Conventional controllers; Monitoring and controlling; Research and development; Sustainable energy; Energy management systems